Material matters : new materials in design - Howes, Philip, 1985- (Black Dog Pub., 2012)
"Material Matters: New Materials in Design discusses the vast range of materials that are available to us today, and highlights the advances predicted to prove seminal in the future. The six chapters are divided by chemical composition--Metals, Glasses, Ceramics, Polymers, Composites and material Futures--and with every material featured, the book stresses the relevance of physical material properties. Each material featured is presented with relevant manufacturer information, material properties and current and potential applications and includes the websites of manufacturers and research institutes, making this a handy reference book for the designer. Material examples include the newly developed metallic 'microlattice', now the lightest solid known on earth; Dow Corning's 'Deflexion', a fabric capable of instantly hardening and Graphene, a material which, at 200 times the strength of structural steel despite being only one atom thick, has the potential to revolutionize the field of electronics. Philip Howes, Materials Scientist and Zoe Laughlin, Creative Director of The Institute of Making, provide explanations of the basic chemical structure of materials--what makes a glass a glass and why not all polymers are plastics. Their discussion of the potentialities of new materials embraces disciplines as disparate as aerospace engineering and medical research, in addition to offering explanations to everyday material conundrums." -- Publisher's description.